The imagination machine how to spark new ideas and create your company's future - Martin Reeves and Jack Fuller (Boston, Massachusetts Harvard Business Review Press, 2021)
We need imagination now more than ever - to find opportunities in adversity, rethink our businesses, and discover new paths to growth. Yet too many companies have lost their ability to imagine. What is this mysterious capacity? How does imagination work? And how can organizations keep it alive and harness it systematically?
Includes Index
Keywords: Imagination